ANALISIS PENGEMBANGAN PRODUK CHARGER HANDPHONE DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD): NALYSIS OF HANDPHONE CHARGER PRODUCT DEVELOPMENT USING QUALITY FUNCTION DEPLOYMENT (QFD) METHOD - Albertus Laurensius Setyabudhi; Evis Saputra (YCMM, 2020)
One of the technological tools that are currently developing is a cell phone or cellphone. Although mobile phones are sophisticated tools, mobile phones are electronic devices that require batteries as their main energy source. This research produces an analysis of product development that meets consumer needs using the Quality Function Deployment (QFD) method. The selection of this method is based on user involvement. This study aims to analyze the product development of electromagnetic mobile phone charger technology so that it becomes an effective and efficient product. This product development analysis using the House of Quality method from Quality Function Deployment (QFD) is carried out by looking at the user's wishes and translating it into technical language (technical characteristics). Obtained 6 attributes and 6 technical characteristics. The characteristics of the quality of the material are characteristics that are difficult on the level of difficulty and are quite expensive in terms of cost estimates, for others, they are quite easy on the level of difficulty and cheap in terms of cost. Based on the development of the concept, the product design has a function to charge cellphones, as a promotional media, in an original and unique form, using ABS plastic material and using magnets. So this product is very useful for users to use it flexibly.